Effect of Seedling Density on Growth Characteristics of Cabbage (Brassica oleracea var. capitata) cv. kf-65 in Nursery - Bikesh Thapa; Dharmaraj Katwal (Turkish Journal of Agriculture: Food Science and Technology, 2024)
Crop yield is largely influenced by the seedling quality and establishment. Seedling density is an important factor that plays a vital role in producing quality seedlings. Seedling growth characteristics of cabbage cv. kf-65 was evaluated at four inter row and intra row spacing: 0.5cm×1.0cm, 1.0cm×1.0cm, 1.5cm×1.5cm, and 2.0cm×2.0cm in the field of Institute of Agriculture and Animal Science, Lamjung Campus during September-October, 2018. Seed germination was 96% under a partially controlled germinator in the lab whereas mean germination in the field was found to be 62%. Treatments were laid out in Randomized Complete Block Design with five replications. Data was collected after 23 days using the destructive sampling method. Plant height, leaf number, leaf area, fresh shoot and root weight and % dry matter was recorded from five samples from each replication of every treatment. Plant population had a significant effect on plant leaf area, fresh shoot and root weight and % dry weight. The 2.0cm×2.0cm spacing had significantly higher leaf area (25.3cm2), fresh shoot (1.33g) and root weight (0.06g). Dry weight % (23%) was significantly higher for 1.5cm×1.5cm spacing. The result indicates that wider spacing (≥ 2cm) was found to be favourable to obtaining robust and quality seedlings.